Effect of protease inhibitor from Agaricus bisporus on glucose uptake and oxidative stress in 3T3-L1 adipocytes - Vishvakarma R.; Mishra A. (My University, 2025)
Objective: To explore the effect of the protease inhibitor from Agaricus bisporus (J.E. Lange) Imbach (AbPI) on glucose uptake and oxidative stress in 3T3-L1 adipocytes. Methods: Adipocytes were differentiated and stained with Oil-Red-O staining to confirm adipogenesis. The toxic/protective effect of AbPI on the adipocytes was determined by MTT assay, intracellular reactive oxygen species generation through flow cytometry, and morphologically through confocal microscopy using propidium iodide, 4,6-diamino-2-phenylindol dihydrochloride, and 2',7'-dichlorofluorescein diacetate dyes. The uptake of fluorescent glucose analog, 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl) amino]-2-deoxy-d-glucose by adipocytes was also studied through confocal microscopy. Results: MTT assay showed that the cell survival rate was (28.00±3.00)%, (92.33±2.60)%, and (71.34±2.10)% in the presence of 2 mM H2O2, AbPI alone, and AbPI and H2O2 both, respectively, in comparison to the control. Oil-Red-O staining indicated that AbPI enhanced adipogenesis. AbPI stimulated the glucose uptake by adipocytes similar to the drug rosiglitazone, and showed insulin-sensitizing effect in the presence of insulin, but failed to stimulate the uptake in the absence of insulin. Intracellular reactive oxygen species generation was reduced in differentiating adipocytes upon AbPI treatment. Confocal microscopy showed that the damaged cell population rose to 3.50%, 117.84%, and 261.50% in the presence of AbPI alone, AbPI with H2O2, and H2O2 alone, respectively. Conclusions: The protease inhibitor enhances glucose uptake by adipocytes and exhibits a cytoprotective effect on them. © 2020 Wolters Kluwer Medknow Publications. All rights reserved.